Masalah Pembiayaan Pendidikan di Indonesia: Kenaikan Biaya Pendidikan - Arsal, Fathur Riyadhi; Hidayat, Ara (Invention: Journal Research and Education Studies, 2024)
The cost of education is becoming increasingly expensive. According to an article quoted by detikedu citing BPS statistics, the cost of education rises by 10% to 15% each year. It should be realized that unequal education as a result of the high cost of education will affect all elements of social life. Education is not only expensive in public and private schools or educational institutions. This research uses a literature research approach. The literature search used keywords such as "education financing problems in Indonesia", "rising education costs", "high education costs", and other keyword combinations relevant to the topic. Education financing consists of investment costs, operating costs and personal costs. One of the most important aspects of achieving optimal educational goals is managing expenditure appropriately in accordance with the necessary financing needs. It is a sad reality that, due to lack of resources, disadvantaged children will continue to drop out of primary, junior secondary and senior secondary school, and will never have the opportunity to go to university. Some factors that contribute to the rising cost of education include: 1) Ineffective and inefficient school financing budgets, 2) Lack of democratization and transparency in school management, 3) Weak supervision and control of school fees by the government, 4) Lack of teacher welfare.